Benzoyl peroxide + chlorhexidine versus chlorhexidine alone skin preparation to reduce Propionibacterium acnes: a randomized controlled trial. Issue 11 (8th October 2018) - Hancock, Douglas S.; Rupasinghe, Shavantha L.; Elkinson, Ilia; Bloomfield, Max G.; Larsen, Peter D.
Abstract : Background: Traditional skin preparation for shoulder surgery is not specific for Propionibacterium acnes . Topical benzoyl peroxide for 48 h preoperatively has been shown to reduce the bacterial load of P. acnes on the skin. Our aim was to investigate whether skin preparation with a single application of benzoyl peroxide combined with 2% chlorhexidine/alcohol immediately prior to surgery was superior to 2% chlorhexidine/alcohol alone at inhibiting P. acnes . Methods: We conducted a single‐blinded interventional study. Each shoulder of the participant was assigned a different preparation through a randomization process. Two sites were assessed per shoulder. The intervention was the application of benzoyl peroxide followed by chlorhexidine/alcohol to the shoulder. The control was two applications of 2% chlorhexidine/alcohol. Superficial skin swabs for semi‐quantitative culture were taken pre‐ and post‐skin preparation. Results: A total of 22 male participants were randomized. All participants were colonized with P. acnes on baseline swabs. We found complete inhibition of P. acnes at 14 days at 80% of sites prepared with benzoyl peroxide + chlorhexidine/alcohol compared with 86% inhibition at shoulder sites prepared with chlorhexidine alone. Conclusion: There was no reduction in the growth of P. acnes over 14 days with chlorhexidine/alcohol and benzoyl peroxide compared with chlorhexidine alone. On the basis of these results, the addition of benzoyl peroxide at the time of surgery does not appear to increase the efficacy of the surgical preparation for inhibiting P. acnes growth.